Rekreasyon Lisans Programlarında Ders Etkililiği: Tanımlayıcı Araştırma. - ŞİMŞEK, Kerem Yıldırım; KOLOĞLU, Deniz Raha; YILDIZ, Furkan Ufuk (Turkiye Klinikleri Journal of Sports Sciences, 2022)
Objective: In higher education, the only department where management and application are tried to be taught in 2 different faculties (faculty of sports sciences/faculty of tourism) is recreation. Considering this important structural problem; it can easily be concluded that recreation undergraduate programs are not sufficient enough to meet the needs of the sector and recreation experts. The curricula are not structured in accordance with the sector needs, which weakens the effectiveness of lessons taught in the recreation undergraduate programs. In this context, the purpose of this research is to determine the effectiveness of occupational lessons taught in the recreation undergraduate programs on raising recreation experts. Material and Methods: Target population of the research consists of recreation programs in the Higher Education Institutions. Sports science faculty recreation undergraduate programs in Eskişehir, Ankara, Kırıkkale, Sakarya provinces were selected from the population with the criterion-based sampling technique and a total of 26 students were chosen. The research was designed as a case study, which is among qualitative research models. In order to collect data concerning the effectiveness of lessons in the recreation undergraduate programs, a semi-structured interview form developed by the researchers was used. Content analysis technique was used for the analysis of the research data. Measurement triangulation, observation triangulation, expertization, detailed description, intercoder reliability and confirmation examination were performed for the validity and reliability of the data. Results: As a result of the analysis, it was determined that theoretical and applied lessons did not prepare the students enough, the way of teaching and presenting the lessons was sufficient, theoretical and applied lessons partially prepared them to the profession and theoretical lesson contents did not prepare them to the profession. Conclusion: As a consequence, it is possible to state that lesson effectiveness in the recreation undergraduate programs is not sufficient. In order to develop lesson effectiveness, it is required to reduce excessive theoretical knowledge, pay strict attention to including the components of theory and practice in lessons and to increase the credits and durations of professional knowledge lessons.